A literature review and classification of the studies on "halal" in Islamic business journals (2010-2018). Issue 5 (6th June 2020) - Baran, Tamer
Abstract : Purpose: The purpose of this paper is to review the literature on halal research and conduct a content analysis of the same for the purpose of classification, as well as providing a comprehensive bibliography. Design/methodology/approach: This literature review study covers 56 articles published in four journals between the years of 2010-2018. Journals indexed were from the Clarivate Analytics and Scopus databases and included at least one of the words "business", "finance", "management" and "marketing" together with the word "Islamic" in the title. Content analysis was used for the review of the articles and was carried out by two independent researchers with PhD degrees. Leonard's (2001) approach was used to classify the articles. Findings: The findings show that the number of studies into halal has increased in recent years. Moreover, it is found that studies have been conducted mainly in certain countries and specific sectors. Furthermore, one of the most important findings is that there are no denomination-based researches on halal in the journals included in the study. Research limitations/implications: The findings of this study can be generalized only for the selected databases, journals and given period but not for all of the halal literature. Besides the research categories in the current study, further research can be conducted into various disused areas in terms of industry, country of study, product, denomination, etc. Practical implications: The paper provides a comprehensive bibliography that will be useful, especially to researchers studying existing research and for contemplating future research. Originality/value: This is the first paper that provides a comprehensive literature review and classification of halal literature for the period 2010-2018.